STUDI ATAS PRAKTIK AKUNTANSI DI ORGANISASI PIASJID DI SURABAYA - Pepie Diptyana (STIE Perbanas Surabaya, 2011)
Studies in accounting are important especially in any organization that deals with operation that spends money. In this emerging public sector, especially of accounting it is assumed that there are limited studies in nonprofit accounting, especially in religion organization. This research explores the process of accounting practice in mosque organization. There are somefindings: first, accounting process is required by Al-Qur'on, so it is a mosque organizationb obligation to report its resources use as an accountability practice, second, mosque organizations use cash basis to provide its financial report, third, financial report in mosque organization is a summary of cash bookkeeping.